Beyond Spin: Exploring The Role of Internal Communicationin Creating Meaning Around Corporate Social Responsibility - Chauvin, Matthieu (2009)
This research identifies an important gap in the CSR literature: there are no theories to account for the way in which organisations use their internal communication to create meaning around CSR. Based on a review of the literature and a participant-observation in an engineering consultancy, this exploratory paper presents an attempt at theory development in this field, by drawing on the concepts of sensemaking (Weick, 1995), sensegiving (Gioia & Chittipeddi, 1991), and enactment (Weick, 1979).